Competitive Advantage Strategy in Improving Corporate Performance of Stevedoring Company (Samudera Stevedoring) - Yunanto Dwi; Derriawan Derriawan; Zulkifli Zulkifli (Jurnal Logistik Indonesia, 2021)
The purpose of this study was to see the influence of HR competence, equipment facility and innovation directly or indirectly on competitive advantage, and the influence of all these variables on corporate performance of Stevedoring Company (Samudera Stevedoring). The research sample was 60 respondents who were management level of Samudera Stevedoring. The sampling technique was purposive sampling. Data collection using questionnaires and FGD. The data were analyzed using Structural Equation Modeling (SEM) analysis processed with SmartPLS software. The results of the study prove that the variables of HR competence, equipment facility and innovation have a significant influence on competitive advantage and competitive advantage has significant influence on corporate performance. While HR competence variable has a significant influence on corporate performance, however the equipment facility and innovation variables have no significant influence on corporate performance. The research result also shows the corporate performance plan by referring to the strategies from the analysis that has been done and the right strategy is selected, namely strengthen of HR competence